Penggunaan Media Sosial oleh Anak di Bawah Umur di Kota Palangka Raya Perspektif Maqashid Syariah - Hikmal Asril Annaza; Khairil Anwar; Rafik Patrajaya (Dinasti Research, 2026)
The use of social media by minors continues to increase along with the development of digital technology and has various implications for the development of religion, intellect, spirit, character, and social behavior of children. This research aims to analyze the use of social media by minors from the perspective of maqashid sharia. This research uses a qualitative method with an empirical-normative approach. Data were obtained thru semi-structured interviews with ten children aged 12–15 years and five teachers in the city of Palangka Raya, selected using purposive sampling techniques, and then analyzed thru data reduction, data presentation, and conclusion drawing with a maqashid syariah approach. The research results show that social media provides benefits as a means of obtaining information, learning, and communication. However, it was found that 7 out of 10 children experienced a decrease in learning concentration and often lost track of time, 6 out of 10 used social media while studying, 5 out of 10 had delayed prayers, all respondents had been exposed to content contrary to religious teachings, 8 out of 10 had seen negative content, 4 out of 10 imitated behaviors seen on social media, and 6 out of 10 showed tendencies toward consumerist behavior. This shows that the use of social media has more negative impacts on underage children. These findings are reinforced by interviews with teachers who state that uncontrolled use of social media affects students' discipline, behavior, social interaction, and academic performance. This research emphasizes that the assessment of social media within the framework of maqashid syariah is determined by the purpose of its use and the impact it has on the welfare of children.